Kompetensi Guru Fikih dalam Merencanakan Media Pembelajaran di Madrasah Aliyah Negeri 1 Medan - Sholehah SN, Nur Rahmadhani; Lessy, Zulkipli (Nusantara: Jurnal Pendidikan Indonesia, 2024)
Purpose – This study aims to determine the competence of fiqh teachers in planning fiqh learning media in MAN 1 Medan starting from methods, suitability of achievement indicators following the conditions and situations of students, and constraints and solutions of fiqh teachers in planning learning media.Method – The research method that researchers use is qualitative research that produces descriptive data in the form of words from people and behavior that is being observed with a phenomenological approach. Data collection is used with observation, interviews, and documentation studies.Findings – The results showed that the competence of fiqh teachers in planning learning media in MAN 1 Medan showed good competence. The use of learning media carried out by MAN 1 teachers uses learning videos, PowerPoint slides, images or posters, and media from practical materials. The obstacles found by fiqh teachers in planning fiqh learning media in MAN 1 Medan are time constraints. This is less conducive to students. Lack of teachers' ability to use media that varies in access to knowledge and technology. The solution is using multi-strategy, multi-method, teachers must attend various trainings throughout digital learning media. Research Implications – This research makes a positive contribution to the school. To be able to improve the competence of fiqh teachers in planning learning media, which is carried out in various ways, such as by attending media training.